2023
DOI: 10.1080/22221751.2023.2165970
|View full text |Cite
|
Sign up to set email alerts
|

The nasopharyngeal microbiome in COVID-19

Abstract: The development of novel culture-independent techniques of microbial identification has allowed a rapid progress in the knowledge of the nasopharyngeal microbiota and its role in health and disease. Thus, it has been demonstrated that the nasopharyngeal microbiota defends the host from invading pathogens that enter the body through the upper airways by participating in the modulation of innate and adaptive immune responses. The current COVID-19 pandemic has created an urgent need for fast-track research, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 88 publications
(134 reference statements)
6
40
0
Order By: Relevance
“…Among these different areas, the nasopharynx is anatomically unique because it presents a common meeting place for the ear, nose, and mouth cavities [ 15 ], but has not gained special prominence until the outbreak of the current COVID-19 pandemic [ 16 ]. Importantly, dozens of studies have already detected unquestionable correlations between the composition of the nasopharyngeal microbiota and susceptibility to different viral infections in humans [ 13 ], and some evidence is emerging, although still controversial, that it may be playing a role in the susceptibility to SARS-CoV-2 infection, too [ 17 ]. Elucidating this might shed light on the still unexplained fact that some COVID-19 patients, such as the elderly, are more susceptible and present more severe forms of COVID-19 than others [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these different areas, the nasopharynx is anatomically unique because it presents a common meeting place for the ear, nose, and mouth cavities [ 15 ], but has not gained special prominence until the outbreak of the current COVID-19 pandemic [ 16 ]. Importantly, dozens of studies have already detected unquestionable correlations between the composition of the nasopharyngeal microbiota and susceptibility to different viral infections in humans [ 13 ], and some evidence is emerging, although still controversial, that it may be playing a role in the susceptibility to SARS-CoV-2 infection, too [ 17 ]. Elucidating this might shed light on the still unexplained fact that some COVID-19 patients, such as the elderly, are more susceptible and present more severe forms of COVID-19 than others [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID-19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response. [83][84][85] 3. 1.3 Changes in microbiota and immune microenvironment SARS-CoV-2 infection is associated with intestinal inflammation, intestinal barrier disruption, and changes in lipid metabolism.…”
Section: Changes In the Microbiota Of The Upper Respiratory Tractmentioning
confidence: 99%
“…Nasopharyngeal microbiota may be associated with SARS‐CoV‐2 infection. Analysis of nasopharyngeal microbiota abundance in hospitalized patients with COVID‐19 and healthy controls found that some gut microbiota and nasopharyngeal microbiota participate in the host immune response 83–85 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…Even through the respiratory microbiota had not been so studied as that of other anatomical areas, such as the gut, due to the old paradigm that lungs were sterile (13,14), recent studies have demonstrated that changes in the nasopharyngeal microbiota clearly correlate with increased or reduced susceptibility to different viral infections in humans (13). Indeed, focusing on COVID-19 research, dozens of studies have already tried to elucidate whether SARS-CoV-2 infection or the COVID-19 disease severity are associated with changes in the nasopharyngeal microbiota (14). However, unfortunately, the analysis of all these previous studies 3 reveals extremely variable and contradictory results, which prevent solid and reliable conclusions from being drawn (14).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, focusing on COVID-19 research, dozens of studies have already tried to elucidate whether SARS-CoV-2 infection or the COVID-19 disease severity are associated with changes in the nasopharyngeal microbiota (14). However, unfortunately, the analysis of all these previous studies 3 reveals extremely variable and contradictory results, which prevent solid and reliable conclusions from being drawn (14).…”
Section: Introductionmentioning
confidence: 99%